Novel and selective potentiometric sensors for Cinchocaine HCl determination in its pure and Co-formulated dosage form: A comparative study of in situ carbon sensors based on different ion pairing agents. (March 2021) - Elashery, Sally E.A.; Frag, Eman Yossri; Sleim, Ashraf A.E.
Highlights: Promising in situ carbon sensors have been fabricated for cinchocaine HCl detection. A comparative study of the sensors based on various ion pairing agents was conducted. The sensors achieved superior Nernstian behavior over a wide concentration range. The sensors were applied for the CIN.HCl detection as co-formulated with other drugs. Abstract: Promising in situ carbon paste electrodes (ICPEs) have been fabricated for selective cinchocaine HCl (CIN.HCl) determination in its pure form and as co-formulated with other drugs in its pharmaceutical preparation (Otal). The fabricated ICPEs were modified with various ion pairing agents as sodium tetraphenylborate (NaTPB), phosphotungstic acid (PTA), phosphomolybdic acid (PMA) and ammonium reineckate (RN) as an electroactive material. A comparative study of the established ICPEs based on 6 mg PMA (electrode I), 6 mg PTA (electrode II) and 9 mg RN (electrode III) ion pairing agents was conducted with considering the optimization of the developed sensors performance characteristics. The developed sensors I, II and III exhibited a fast and linear response for the monovalent CIN.HCl drug over the spacious concentration range from 1.0 × 10 –5 to 1.0 × 10 –2 mol L -1 achieving superior Nernstian slope values of 59.80 ± 0.14, 59.20 ± 0.10 and 59.20 ± 0.24 mV decade -1, respectively, reflecting no deviation from the Nernstian behavior over the pH range of 2.5–7. The aforementioned sensors displayed a good distinguishing power for CIN.HCl over the other cations, sugars and other co-formulated drugs. Additionally, validation parameters have been studied according to the IUPAC recommendations. The proposed electrodes have been employed with a promising success for determining CIN.HCl in Otal (ear drop) with good relative standard deviation values. Moreover, the inter- and intra-day accuracy (expressed as recovery %) and precision (expressed as relative standard deviation %) of the established CIN.HCl selective potentiometric method have been studied. As, the inter-day accuracy and precision ranges were found to be 99.46–100.1, 99.59–99.90 and 99.58–100.3% and 0.315–0.844, 0.263–1.199 and 0.328–0.703% while the intra-day accuracy and precision ranges were 99.62–101.4, 99.59–100.5 and 99.71–100.5% and 0.263–1.220, 0.471–0.877 and 0.528–0.885% for the established sensors I, II and III in the CIN.HCl pharmaceutical form (Otal), respectively.